Quality of life of end stage renal failure patients undergoing dialysis treatment in Hospital Universiti Sains Malaysia (Hospital USM) - Naser, Wan Nor Amira Mohd (Universiti Sains Malaysia, 2013)
End Stage Renal Failure (ESRF) is a chronic kidney disease that requires for Renal Replacement Therapies (RRT) due to irreversible loss of almost total renal function. Renal replacement therapy is important to avoid life-threatening complication such as uremia and heart failure as well as to prolong patients' quality of life by slowing down the disease progress. The most common RRT opted by patients are Peritoneal Dialysis (PD) and Haemodialysis (HD). Dialysis treatment however, may also causes highly abnormal life lead the patient as they experience many changes on physical. psychological and social functioning that attribute by both the disease process and their ability to cope with such changes. The aim of this study is to evaluate the impact ol dialysis treatment on patients’ quality of life (QoL) and the overall patients' QoL in Hospital Universiti Sains Malaysia (Hospital USM). A cross-sectional survey was conducted among ESRF patients in two medical wards and Haemodialysis Unit. Hospital USM. Respondent for this study was selected purposively while receiving dialysis treatment. Data was collected within one month period from 15 February 2013 to 15 March 2013 using a set of questionnaire of which consisted of self-developed and validated questionnaire, the WHOQOL-BREF (Malay version). Data was analysed using SPSS version 12.0. Overall. 50 ESRF patients involved in the study (PD. n=17; HD. n=33). Educational level, occupation and family income were found to be significantly associated to patients' QoL. The greater dialysis impact of ESRF patients were psychological and environment. Findings also revealed that ESRF patients' who had experienced greater impact of dialysis treatment had good QoL score. Both PD and HD groups had good QoL (62%). Thus, future research is needed to re-evaluate these findings in further detail.